Mapping the hemodynamic response in human subjects to a dopaminergic challenge with dextroamphetamine using ASL-based pharmacological MRI - Schouw, M.L.J.; Kaag, A.M.; Caan, M.W.A.; Heijtel, D.F.R.; Majoie, C.B.L.M.; Nederveen, A.J.; Booij, J.; Reneman, L. (NeuroImage (Orlando, Fla.), 2013)
Pharmacological magnetic resonance imaging (phMRI) maps the neurovascular response to a pharmacological challenge and is increasingly used to assess neurotransmitter systems. Here we investigated the hemodynamic response to a dopaminergic (DAergic) challenge with dextroamphetamine (dAMPH) in humans using arterial spin labeling (ASL) based phMRI. Twelve healthy male subjects aged 21.0years (±1.5) were included. We used a pseudo-continuous ASL sequence (40min) to quantify cerebral blood flow (CBF) and started dAMPH infusion (0.3mg/kg) after 10min. On another day, we measured baseline dopamine D2/3 receptor availability with [123I]IBZM single photon emission computed tomography (SPECT). Baseline measures on mood and impulsivity and subjective behavioral responses to dAMPH were obtained. CBF response was corrected for cardiovascular effects using an occipital cortex mask for internal reference. Corrected CBF (sCBF) was analyzed using ROI-based and voxel-based analysis, in addition to independent component analysis (ICA). CBF data was correlated to D2/3 receptor availability and behavioral measures. Subjects reported experiencing euphoria following dAMPH administration. In the striatum sCBF significantly increased, as demonstrated by all three analysis methods. Voxel-based analysis and ICA also showed increased sCBF in the thalamus, anterior cingulate and cerebellum. Decreased sCBF was observed in several cortical areas, the posterior cingulated and paracingulate cortex. Apart from one ICA component, no correlations were found with sCBF changes and D2/3 receptor availability and behavioral measures. Our observations are in line with literature and provide further evidence that ASL-based phMRI with dAMPH is a promising technique to assess DAergic function in human subjects. ► We investigated effects of acute dexamphetamine challenge on CBF in humans. ► 12 healthy males received 0.3mg/kg dexamphetamine i.v. causing euphoric response. ► CBF corrected for vascular effects and analyzed ROI-based, voxel-based and with ICA ► Specific CBF increased in dopaminergic areas as striatum, thalamus and ACC. ► These results show phMRI as a promising technique to map the dopaminergic response.